2-Arachidonoylglycerol ameliorates inflammatory stress-induced insulin resistance in cardiomyocytes - Chanda, Dipanjan (J Biol Chem, 2017)
Several studies have linked impaired glucose uptake and insulin resistance (IR) to functional impairment of the heart. Recently, endocannabinoids have been implicated in cardiovascular disease. However, the mechanisms involving endocannabinoid signaling, glucose uptake, and IR in cardiomyocytes are understudied. Here we report that the endocannabinoid 2-arachidonoylglycerol (2-AG), via stimulation of cannabinoid type 1 (CB1) receptor and Ca(2+)/calmodulin-dependent protein kinase β, activates AMP-activated kinase (AMPK), leading to increased glucose uptake. Interestingly, we have observed that the mRNA expression of CB1 and CB2 receptors was decreased in diabetic mice, indicating reduced endocannabinoid signaling in the diabetic heart. We further establish that TNFα induces IR in cardiomyocytes. Treatment with 2-AG suppresses TNFα-induced proinflammatory markers and improves IR and glucose uptake. Conversely, pharmacological inhibition or knockdown of AMPK attenuates the anti-inflammatory effect and reversal of IR elicited by 2-AG. Additionally, in human embryonic stem cell-derived cardiomyocytes challenged with TNFα or FFA, we demonstrate that 2-AG improves insulin sensitivity and glucose uptake. In conclusion, 2-AG abates inflammatory responses, increases glucose uptake, and overcomes IR in an AMPK-dependent manner in cardiomyocytes.